The Effectiveness of Tri Hita Karana Based Digital Comics in Shaping Students' Global Diversity and Independence - I Gede Astawan; I Nyoman Laba Jayanta; Ni Made Dyan Anggreni (Indonesian Values and Character Education Journal, 2025)
Character formation at the elementary school level is a priority in the Indonesian education system however, its implementation remains less balanced compared to cognitive achievement. This study aims to examine the effectiveness of Tri Hita Karana based digital comic learning media in enhancing students’ global diversity and independence. The research employed a quasi-experimental design with a non-equivalent post-test only control group. The participants were divided into two groups: an experimental group that used digital comics and a control group that received conventional instruction. Data were collected through validated questionnaires and analyzed using Multivariate Analysis of Variance (MANOVA). The results revealed a significant difference between the two groups (p < 0.05), with a stronger improvement in global diversity (η² = 0.457) than in independence (η² = 0.097). These findings indicate that integrating local cultural values into digital media effectively strengthens students’ cognitive, affective, and social character development. This study implies that local wisdom based digital comics can serve as an innovative strategy for character education in elementary schools and support the contextual and meaningful implementation of the Pancasila Student Profile.